Perancangan dan Simulasi Mesin Perontok Biji Jagung Kapasitas 400 Kg/Jam - Azzah Rosadi, Nabilla; Ulhafidzah, Annisa; Yuliarman, Yuliarman; Menhendry, Menhendry; Yetri, Yuli (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Corn is one of the main sources of carbohydrates in Indonesia. Corn growth has reached all regions of the archipelago. As a source of carbohydrates other than rice, corn can also be processed into various food industry products such as snacks. In addition, corn can also be used as animal feed so the need for shelled corn is very high in Indonesia. Therefore we need an appropriate technology that functions to facilitate human work to produce shelled corn in a short time and high production yields. So Corn Seed Threshing Machine was designed with a capacity of 400 kg/hour. This machine consists of main components such as a cylinder shell, funnel, guide, and reservoir. This machine uses a 1.5 HP electric motor with a rotation of 1400 rpm and uses a Belt and Puli transmission system. The sheller shaft is added with a spiral-shaped sheller tooth.